Metabolizable Energy of Whole and Ground Canola Seed with Enzyme Supplementation and Effects of Ground Canola Seed on Broiler Performance - de Souza, Cleverson; Nunes, Ricardo Vianna; de Souza, Cleison; Cesar, Paula Horácio; Lovatto, Francieli Sordi; Bedin, Aline Felix Schneider; Suyama, Marcelo Suzuki [UNESP]; Gewehr, Clóvis Eliseu (MDPI, 2025)
Canola seed is a high-energy oilseed with potential as an alternative feed ingredient in broiler diets, yet its use is limited by nutrient encapsulation and antinutritional factors. This study aimed to evaluate the apparent metabolizable energy (AME) of canola seed and its effects on broiler performance, organ development, serum biochemical profile, and carcass yield from hatch to 42 days of age. A digestibility trial was conducted using 300 broilers in a 2 × 2 × 2 factorial design (whole vs. ground seed, with or without enzyme, at 100 or 200 g/kg replacement). A performance trial involved 660 broilers fed diets with 0, 50, 100, 150, 200, and 250 g/kg of ground canola seed (GCS). Grinding without enzyme addition significantly increased AME from 2318 to 3864 kcal/kg and AME corrected for nitrogen retention (AMEn) from 2192 to 3734 kcal/kg (p < 0.05). An interaction was observed between seed x enzyme and seed × levels (p < 0.05). Addition of enzymes increased the AME value of canola from 3091 to 4091 kcal/kg and the AMEn value from 2963 to 3958 kcal/kg (p < 0.001). Inclusion of GCS up to 150 g/kg did not affect feed intake, feed conversion ratio (FCR), organ index, serum parameters, or carcass traits (p > 0.05). However, higher inclusion levels (200 and 250 g/kg) reduced body weight (BW) and body weight gain (BWG) and worsened FCR, particularly in the early growth stages (p > 0.05). In the period 1-42 days of age, only the 250 g/kg level worsened FCR (p < 0.001), and BWG decreased in 200 and 250 g/kg (p < 0.001). In conclusion, GCS can be included up to 150 g/kg in broiler diets without compromising performance or metabolism, and grinding combined with enzyme supplementation enhances its nutritional value.